Potential contribution of diabetes mellitus to orthostatic blood pressure fall and conversion of mild cognitive impairment to dementia - Muratli S (Dove Medical Press, 2016)
Sevilay Muratli,1 Fatih Tufan,1 Ozlem Soyluk,2 Gulistan Bahat,1 Mehmet Akif Karan1 1Department of Geriatrics, 2Department of Endocrinology, Istanbul Faculty of Medicine, Istanbul University, Istanbul, TurkeyWe read the article “Orthostatic blood pressure in people with mild cognitive impairment predicts conversion to dementia” by Hayakawa et al1 with interest. It is well-known that many individuals with mild cognitive impairment (MCI) progress to dementia.2 However, we do not exactly know which risk factors increase this risk and to what extent. Hypertension is a risk factor for Alzheimer’s disease and vascular dementia. However, the findings of this study make us consider hypotension as a new risk factor for dementia. Furthermore, a recently published 6-year prospective general population cohort study suggested that not only orthostatic hypotension (OH), but also symptoms of OH seemed to be risk factors for cognitive decline.3 Notably, in the study by Elmstahl et al3, hypertension and diabetes mellitus (DM) were more common in subjects with dementia. We would like to make some comments on this well-designed study.